The State of State Surveillance in Europe - Findings from a Cross-National Study on Data Retention in 25 Countries - Alena Birrer; Danya He; Natascha Just (International Telecommunications Society (ITS), 2023)
"We kill people based on metadata" - this statement by the former head of the American National Security Agency (NSA) Michael Hayden captures the potentially severe impacts of communications metadata surveillance. Such data, i.e., information on who communicates with whom, for how long, where, and through which device, have enabled states to identify suspicious patterns in communications (Murray & Fussey, 2019). In recent years, governments have instrumentalized extraordinary events and crises to further expand the mass monitoring of communications metadata, for example during the COVID-19 pandemic (Lyon, 2022) or in the ongoing quest to protect children online (e.g., the European Commission's proposal to require certain online communications service providers to monitor even encrypted private communication, COM(2022) 209 final). (...)
Keywords: 330